2014
DOI: 10.1080/19371918.2014.938396
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Resilience in the Lives of Adults with Sickle Cell Disease

Abstract: This qualitative study focused on the experiences of adults living with sickle cell disease (SCD) in the New York City area. Twenty-three individuals participated in one of three focus groups. The purpose of this study was to learn if appropriate health care for individuals with sickle cell disease, based on years of research, has been implemented. The findings indicate that best practices in the treatment of SCD are often not followed by medical personnel. Critical race theory provides a framework to understa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…The chronicity and rapidity of these pain episodes reduce sickle-cell disease patients’ quality of life 4,6,9. Because sickle-cell disease predominantly affects minority populations, the manifestations of the disease exacerbate the challenges faced by communities with high proportions of minority residents 10. This motivated us to develop a protocol of care in an effort to improve the medical care provided to the sickle-cell disease population at our institution.…”
Section: Discussionmentioning
confidence: 99%
“…The chronicity and rapidity of these pain episodes reduce sickle-cell disease patients’ quality of life 4,6,9. Because sickle-cell disease predominantly affects minority populations, the manifestations of the disease exacerbate the challenges faced by communities with high proportions of minority residents 10. This motivated us to develop a protocol of care in an effort to improve the medical care provided to the sickle-cell disease population at our institution.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal hemoglobin impedes the production of red blood cells in SCD. This causes the normally round red blood cell to become elongated and assume the shape of a crescent [4], which results in the decreased flow of red blood cells through the blood vessels to various parts of the body. Over time, this will lead to painful sickle cell crises, anemia, infections, and multiple organ damage [5].…”
Section: Introductionmentioning
confidence: 99%
“…51 Unfortunately, patients with SCD have been misclassified as drug-seekers by providers who are not familiar with this disease and the characteristics of the pain symptoms these patients experience. 23,24 Because recent guidelines restricting opioid use could negatively affect opioid access among this population, the CDC and the Centers for Medicare & Medicaid Services recently acknowledged that pain management for patients with SCD, as well as those with cancer, require special consideration to ensure that patients have access to clinically appropriate opioid therapy. 25,52 Along with these efforts, the strategy for managing opioid use among this population should focus more on reducing pain episodes and complications, rather than on restricting opioid use.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 Although studies have reported that the risks of developing dependence and addiction to opioids are very low among this population, 22 patients with SCD have been misclassified as drug seekers by providers, especially those who are not familiar with this disease, because of their chronic need for narcotic medications during painful events. 23,24 Patients have reported that the enhanced restriction on prescribing opioids, such as the recent guideline published by the Centers for Disease Control and Prevention (CDC), following the current opioid epidemic, further increases the difficulty in using opioids. 20 To address this issue, the American Society of Hematology and other organizations requested that the CDC clearly acknowledge that special consideration is required for the pain management of patients with SCD, as well as those with cancer, in order to ensure appropriate access to opioid therapy.…”
Section: What This Study Addsmentioning
confidence: 99%